Does virtual tourism influence tourist visit intention on actual attraction? A study from tourist behavior in Indonesia - Li-Wei Liu; Chia-Chung Wang; Pahrudin Pahrudin; Achlan Fahlevi Royanow; Chien Lu; Irwan Rahadi (Cogent Social Sciences)
The COVID-19 outbreak has altered how visitors live, including in the tourism sector. The current study investigates tourist behavior in virtual tourism during the COVID-19 pandemic using the framework of the theory of planned behavior (TPB) and behavior intention. The study included 217 people who utilized virtual tourism for tourists’ during the COVID-19 pandemic. The data are analyzed using Structural Equation Modelling Partial Least Squares (SEM-PLS). According to the findings, the TPB framework, such as attitude toward virtual tourism, subjective norms, and perceived behavior control, have a favorable and substantial influence on satisfaction. Satisfaction with virtual tourism significantly influences attitude change and willingness to visit the actual tourist destination. The study’s implications relate to marketers and stakeholders to provide virtual tourism as a promotion tool of a destination in Indonesia for tourists during the pandemic or crises.